(untitled) (Jurnal Ecosolum, 2022)
Landslides are common problems in watershed management due to their social and economic impacts. Landslide susceptibility mapping is needed to identify areas that need priority in the mitigation program. In landslide susceptibility mapping, the most commonly used geological map is regional map, which is not suited for small to medium-sized areas such as the Kladen watershed, in Rembang, Central Java. This study aims to improve the available geological map with a more detailed lithological unit than regional geological maps, and produce susceptibility maps using geological, geomorphological, and land cover variables. A comparison was performed between the results obtained with the regional geological map and the improved geological map. The logistic regression was selected as it has provided high accuracy for landslide hazard analysis, and does not depend on the subjectivity of the researcher. The results of the landslide susceptibility analysis with regional geological maps show that the lithological factor is statistically insignificant, while in the analysis with a more detailed geological map, it was significant and has higher relevancy than the geomorphology and land cover. The predictive performance test of both models with the area under the curve method shows that the improvement of the geological map increases the performance value from 0,704 to 0,782, producing more reliable landslide susceptibilty map.